2019
DOI: 10.3389/fneur.2019.01155
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of the Gut Microbiota in the Pathogenesis of Parkinson's Disease

Abstract: It is well-recognized that the gut microbiota (GM) is crucial for gut function, metabolism, and energy cycles. The GM also has effects on neurological outcomes via many mechanisms, such as metabolite production and the gut-brain axis. Emerging evidence has gradually indicated that GM dysbiosis plays a role in several neurological diseases, such as Parkinson's disease (PD), Alzheimer's disease, depression, and multiple sclerosis. Several studies have observed that PD patients generally suffer from gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 130 publications
(161 reference statements)
1
84
0
1
Order By: Relevance
“…31 Gut microbiota in PD has been addressed in 16 original articles and one abstract (Supporting Information Table S1) 27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and also has been reviewed. 3,48,49 Gut microbiota, however, differ from country to country in composition even among normal subjects, 50 which makes it difficult to compare PD and controls across countries. In order to identify differences in bacterial taxa in PD across countries, we performed 16S ribosomal RNA (rRNA) gene sequencing of fecal samples from 223 PD patients and 137 controls and, subsequently, conducted a meta-analysis of the dataset we generated and four datasets from other countries.…”
mentioning
confidence: 99%
“…31 Gut microbiota in PD has been addressed in 16 original articles and one abstract (Supporting Information Table S1) 27,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and also has been reviewed. 3,48,49 Gut microbiota, however, differ from country to country in composition even among normal subjects, 50 which makes it difficult to compare PD and controls across countries. In order to identify differences in bacterial taxa in PD across countries, we performed 16S ribosomal RNA (rRNA) gene sequencing of fecal samples from 223 PD patients and 137 controls and, subsequently, conducted a meta-analysis of the dataset we generated and four datasets from other countries.…”
mentioning
confidence: 99%
“…Intestinal bacteria may also be involved in PD where the role of the gut-brain-microbiota axis has been emphasized [44][45][46][47][48][49]. However, this does not exclude involvement of oral bacteria since an oral-brain-microbiota axis may exist, as suggested recently for patients with autism spectrum disorder (ASD) [50].…”
Section: Gingipains and Lipopolysaccharide In Parkinson's Diseasementioning
confidence: 99%
“…A previous study showed that dysfunction of the microbiota‐gut‐brain axis might lead to neurological disease, 1 and increasing evidence indicates a potential bidirectional relationship between gut microbiota and neurological disease. For example, gut microbiota is involved in motor deficits, microglia activation, and pathology, which play important roles in the development of Parkinson's disease 2 . Exchanging gut microbiota can reduce the expression of brain‐derived neurotrophic factor in the brain 3 …”
Section: Parameter Normal Range Fmt Cycles Before Fmt 27 May 2017 Firmentioning
confidence: 99%
“…For example, gut microbiota is involved in motor deficits, microglia activation, and pathology, which play important roles in the development of Parkinson's disease. 2 Exchanging gut microbiota can reduce the expression of brainderived neurotrophic factor in the brain. 3 Faecal microbiota transplantation (FMT) is a microbiota-targeted therapy.…”
mentioning
confidence: 99%